1856 Ala. Laws 17 - (:unkn) unknown (My University, 1856)
That anyone who shall sell or give or lend, to any male minor, a bowie knife, or knife or instrument of the like kind or description, by whatever name called, or air gun or pistol, shall, on conviction be fined not less than three hundred, nor more than one thousand dollars.
Keywords: TRANSFER - MINORS